دور بطاقة الأداء المتوازن في تقييم أداء المؤسسات الاقتصادية - بن خليفة, حمزة (جامعة الوادي - University of Eloued, 2017)
إن بطاقة الأداء المتوازن هي عبارة عن نظام متكامل لقياس وتقييم الأداء للمؤسسات والذي يتكون من مجموعة من المقاييس المالية وغير المالية التي تبين نتائج تنفيذ الأداء وتربطها بإستراتيجية وأهداف المؤسسة المحددة من خلال أربعة أبعاد هي البعد المالي، بعد العميل، بعد العمليات الداخلية وبعد التعلم والنمو، ويمكننا إضافة أبعاد أخرى لحاجة وطبيعة أداء المؤسسة وإستراتيجيتها. ويهدف هذا التقييم إلى التعرف على مواطن القوة وتعزيزها، ومواطن الضعف ووضع الحلول اللازمة لها، ويعتبر هذا النموذج جديد في تقييم أداء المؤسسات الاقتصادية من الناحية المالية وغير المالية . The Balanced Scorecard is an integrated system for measuring and evaluating the performance of the economic enterprises. It consists a set of financial and non-financial measures that show the results of the implementation of performance and relate them to the strategy and goals of the economic enterprise, which is defined through four dimensions : financial dimension, after the client; after internal processes, and after learning and growth. In addition, we can add some other demonsion to the needs and the nature of the entreprises's performance and strategy . The objective of this assessment is to identify, strengthen the strengths, the weaknesses, and to find solution for it. This model is new in the financial and non-financial performance assessing of Economic entreprises
مقال
Keywords: بطاقة الأداء المتوازن، الأداء، تقييم الأداء، المؤسسات الاقتصادية.; Balanced Scorecard, Performance, Performance evaluation, Economic